ANALISIS PENGARUH PROFITABILITAS, LIKUIDITAS, UKURAN PERUSAHAAN, DAN TINGKAT PERTUMBUHAN TERHADAP STRUKTUR MODAL PERUSAHAAN FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA - Kartika, I Komang Sunarta; Dana, I Made (E-Jurnal Manajemen; Vol 4 No 3 (2015), 2015)
ABSTRACT The purpose of this study was to determine the effect of profitability, liquidity, firm size, and growth rate of the capital structure of food and beverage companies listed in Indonesia Stock Exchange. This study uses quantitative research is to look at the financial statements of food and beverage companies published by the Indonesia Stock Exchange in 2010-2013 and found a sample of 10 companies. The sampling technique used purposive sampling technique. Data analysis techniques used in this research is multiple linear regression analysis technique. Retrieved finding that profitability is partially significant negative effect on the capital structure. Liquidity, firm size, and the growth rate is partially significant positive effect on capital structure and profitability, liquidity, firm size and growth rate are simultaneously significant effect on the capital structure.   Keywords : Capital Structure, Profitability, Liquidity, Firm Size and Growth Rate
Keywords: Capital Structure, Profitability; Liquidity; Firm Size; Growth Rate